HARMONY AND FRICTION: THE POPULARITY OF SHALAWAT BADAR AMONG SANTRI - Mashad , Dhurorudin; Ghafur, Muhammad Fakhry (Khazanah: Jurnal Studi Islam dan Humaniora, 2024)
Shalawat Badar is verses composition in Arabic that is dedicated to the Prophet Muhammad. The verses in this verse contain elements of Islamic political ideology. It was composed during a period of significant political upheaval, specifically the era of Guided Democracy (Demokrasi Terpimpin). During this period, Muslims in Indonesia experienced profound political unrest, largely attributable to the growing hegemony of the Indonesian Communist Party (PKI). The present study seeks to contribute to the existing scholarship on Shalawat Badar by offering an analysis of its contemporary spread and popularity. Despite the theological critiques levelled by modern Santri regarding its theological content, which is often seen as bid'ah, Shalawat Badar has witnessed a notable proliferation, defying the obstacles often associated with the dissemination of such works. The findings of this study suggest that Shalawat Badar has gained a widespread presence among Santri from diverse sub-cultures, performed by individuals across various contexts. This paper utilizes a qualitative method, employing a descriptive-analytical approach augmented by literature studies and in-depth interviews with multiple sources, to address the various aspects of Shalawat Badar that are frequently criticized yet still held in various parts of Indonesian.